Critical Media Literacy in the Age of Disinformation: Equipping Students with Tools to Counter Fake News - Yohanes Octovianus L. Awololon; Meenu Sharma (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study investigates the effectiveness of media literacy training in enhancing high school students’ critical evaluation skills in the digital era. The research is motivated by the growing challenges of disinformation and fake news, which often influence young people’s perception of news and their decision-making processes. The objective of this study is to examine how structured media literacy training can transform students’ ability to critically analyze information, recognize fake news, and construct well-founded arguments. A qualitative research approach was employed, using content analysis of training materials, classroom workshops, observations, and reflective interviews or questionnaires to gather data. The participants were purposively selected high school students engaged in the media literacy program. The findings reveal significant improvements in students’ ability to identify the characteristics of fake news, verify information through reliable sources, and analyze media messages more systematically. Before the training, students tended to accept information uncritically, struggled to differentiate between facts and opinions, and relied heavily on social media as their primary source of information. After the training, however, they demonstrated more reflective and cautious behavior, cross-checking information from multiple credible sources and presenting arguments that linked news content with broader socio-political contexts. The study concludes that media literacy training plays a crucial role in equipping students with critical thinking skills necessary to navigate the complexities of the digital information landscape. Furthermore, it emphasizes the need for integrating media literacy into school curricula, supported by teacher training and sustainable educational policies, to ensure long-term resilience against disinformation.